2007
DOI: 10.1007/s11096-007-9136-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pharmacist clinical interventions in a Dutch hospital setting

Abstract: Clinical pharmacy services provided by a junior hospital pharmacist on an internal medicine ward contribute to rationalization of drug therapy and are therefore likely to increase medication safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
53
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 16 publications
8
53
1
2
Order By: Relevance
“…This study supports earlier studies that also demonstrated the value of clinical pharmacists' recommendations for inpatients [2][3][5][6] and outpatients [4].The acceptance rate of the clinical pharmacists' recommendations was higher in our study (90 %) than in other studies (81 % [3], 84 % [4], 82 % [6]). This could have been because we only studied the clinical significance of recommendations emerging from actual drug-related problems and medication errors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study supports earlier studies that also demonstrated the value of clinical pharmacists' recommendations for inpatients [2][3][5][6] and outpatients [4].The acceptance rate of the clinical pharmacists' recommendations was higher in our study (90 %) than in other studies (81 % [3], 84 % [4], 82 % [6]). This could have been because we only studied the clinical significance of recommendations emerging from actual drug-related problems and medication errors.…”
Section: Discussionsupporting
confidence: 91%
“…This is comparable to the results of Overhage and Lukes [5] (pharmacistphysician ranked), and Bosma et al [6] (pharmacist ranked), but is higher than those of Bosma et al [6] (physician ranked) and lower than those of Hatoum et al [3] (pharmacist ranked) and Scullin et al [2] (pharmacist ranked). It is possible that the profession of the person ranking the recommendations could explain some of these differences, since physicians have been shown to rank the clinical significance of pharmacists' recommendations lower than hospital pharmacists [4][5][6]. Five recommendations in our study were ranked 1 (adverse significance).…”
Section: Discussionsupporting
confidence: 85%
“…In our study, an average of 9.8 (median 9) M-DRPs were identified per patient in the intervention group. This was more than three times higher than the number of identified DRPs in other studies conducted in medical wards: Blix et al [24] [28] (82.4 %), but is higher than those of Mannheimer et al [25] (63 %).…”
Section: Discussioncontrasting
confidence: 60%
“…Multiple worldwide studies show high evidence of drug related problems occurring in hospitalized patients. [3][4] However, it has been also been corroborated that upto 50% of these are potentially preventable. 5 Generally, female sex, polypharmacy, renal impairment, age over 65 years and use of narrow therapeutic index (NTI) drugs were identified as risk factors for DRPs.…”
Section: Introductionmentioning
confidence: 99%